2019
DOI: 10.1101/725861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HspA1BIs a Prognostic Biomarker and Correlated With Immune Infiltrates in different subtypes of Breast Cancers

Abstract: Background: Heat shock A1B, also known as HSP70kDa protein 1B, encodes a 70kDa heat shock protein which is a member of the heat shock protein 70 family. HspA1B is a critical gene which related to many type of diseases by involving in the ubiquitin-proteasome pathway. However, the correlations of HspA1B to prognosis and tumor-infiltrating lymphocytes in different cancers remain unclear. Methods: HspA1B expression was evaluated on the Oncomine database and Tumor Immune Estimation Resource (TIMER) site. We analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The HSPA1B protein is a member of the heat shock protein 70 family that encodes a 70 kDa heat shock protein, also known as heat shock protein 70-2 (HSP70-2). HSP70 is a stress-inducible molecular chaperone with key roles that involve polypeptide refolding and degradation [ 40 ]. In our study, the HSPA1B expression was found to be decreased in cancer compared to erythroplakia.…”
Section: Resultsmentioning
confidence: 99%
“…The HSPA1B protein is a member of the heat shock protein 70 family that encodes a 70 kDa heat shock protein, also known as heat shock protein 70-2 (HSP70-2). HSP70 is a stress-inducible molecular chaperone with key roles that involve polypeptide refolding and degradation [ 40 ]. In our study, the HSPA1B expression was found to be decreased in cancer compared to erythroplakia.…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression level of the LPAR6 in various types of cancers was determined via Oncomine, 19 as we previously described. 20 The threshold was set as follows: p-value of 1E-6, fold-change of 2, and gene ranking top 5%.…”
Section: Gene Expression Level Determination Of Lpar6mentioning
confidence: 99%
“…ACE2 is the key enzyme in the renin‐angiotensin system (RAS), both of which are involved in pathological vessel growth and beneficial angiogenesis and it is also related to tumorigenesis 12,13 . Moreover, many researchers have demonstrated that the tumor‐infiltrating lymphocytes (TILs) play an important part in intervening the chemotherapy response and enhancing clinical prognosis especially survival rates of different cancer types, 14,15 such as tumor‐associated macrophages (TAMs) 16–18 and tumor‐infiltrating neutrophils (TINs), and they also impact the outcomes of cancers 19–22 . Therefore, it is also essential to clarify the immunophenotyping of tumor immunocyte interactions and description of novel immunotherapy targets/strategy in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%